Effectiveness of straight arm traction versus operative treatment for displaced paediatric supracondylar humerus fractures: a randomised single-blind controlled, a non-inferiority trial—the STOPUS trial - Mengistu Gebreyohanes Mengesha; Ephrem Gebrehana Adem; Claude F. Martin; William J. Harrison (Trials)
Abstract Background Supracondylar humeral fractures are common injuries in children and can be associated with high morbidity and lead to lifelong disability. The method of treatment affects the risk of complications and potentially the functional outcome. Closed reduction and percutaneous pinning CRPP has become the most widely used treatment method in high-income countries. In the current literature, both CRPP and lateral straight arm traction have been shown to give good results and reasonable levels of complications. The two methods have never been tested against each other in a randomised trial. Furthermore, these methods have not been analysed prospectively in the low and middle income context. Methods The study will be a prospective randomised trial comparing lateral straight arm traction LSAT against CRPP. Recruitment will be at 8 large referral hospitals in Ethiopia. Based on non-inferiority power calculation, we plan to recruit 220 patients. The principal outcome measure will be the PROMIS parent proxy upper extremity short form 8a score version 3.0 at 12 months. The secondary outcome measures will be the Flynn’s criteria; complications; PROMIS parent proxy upper extremity short form 8a score version 3.0 at 6 months; PROMIS parent proxy global health 7 + 2 score version 3.0 administered at 6 and 12 months; and economic analysis of hospital costs for the two treatment modalities. Discussion Supracondylar humeral fractures are common and serious injuries which occur frequently in LMICs where often half the population are under 18 years of age. Such countries have limited capacity for fracture care. Finding solutions which may avoid referral and operative intervention is paramount in developing access to timely and affordable care for all people. If LSAT is non-inferior to CRPP, then children can be treated locally in a cost-effective manner with avoidance of disability. Trial registration ISRCTN Ref 62164933. Registered on 25 July 2024.